Ekonomi Kreatif sebagai Solusi Mengatasi Pengangguran di Era Modern - Yuri, Cicia Oktri; Pratama, Winda Sary; Pratama, Delia Ucha; Rahman, Habib; Zora, Fera (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The creative economy plays an effective role in addressing unemployment in the modern era. The purpose of this article is to analyze how the creative economy can create new job opportunities and empower communities through sectors based on creativity and innovation. The method used is a literature review by examining various sources related to the concept of the creative economy, unemployment challenges, and the role of the government and supporting ecosystems. The main data sources for this research are books and scientific articles sourced from Google Scholar. The data analysis technique used is qualitative data analysis using content analysis. Research findings indicate that the creative economy is capable of creating diverse and sustainable job opportunities, increasing community income, and encouraging innovation and competitiveness in the global market. In conclusion, the development of the creative economy is an appropriate strategy to reduce unemployment in the modern era with the support of integrated policies and the enhancement of human resource capacities.